2016
DOI: 10.1042/bsr20160346
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-9 inhibits high glucose-induced proliferation, differentiation and collagen accumulation of cardiac fibroblasts by down-regulation of TGFBR2

Abstract: To investigate the effects of miR-9 on high glucose (HG)-induced cardiac fibrosis in human cardiac fibroblasts (HCFs), and to establish the mechanism underlying these effects. HCFs were transfected with miR-9 inhibitor or mimic, and then treated with normal or HG. Cell viability and proliferation were detected by using the Cell Counting Kit-8 (CCK-8) assay and Brdu-ELISA assay. Cell differentiation and collagen accumulation of HCFs were detected by qRT-PCR and Western blot assays respectively. The mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…In cardiac fibroblast, miR-9 alleviated proliferation as well as collagen by regulating transforming growth factor b receptor type II (TGFBR2) [33]. Similar results can be seen in our study that transfection with miR-9 inhibitor promoted cell proliferation and collagen production, which was consistent with the previous finding [33]. However, in our study, the regulating relationship between baicalein and miR-9 was validated for the first time.…”
Section: Discussionsupporting
confidence: 92%
“…In cardiac fibroblast, miR-9 alleviated proliferation as well as collagen by regulating transforming growth factor b receptor type II (TGFBR2) [33]. Similar results can be seen in our study that transfection with miR-9 inhibitor promoted cell proliferation and collagen production, which was consistent with the previous finding [33]. However, in our study, the regulating relationship between baicalein and miR-9 was validated for the first time.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore to develop a reliable 3D cardiac tissue model with increased physiological relevance, hESC-derived CMs were mixed with hESC-derived MSCs similar to those likely to be found in human cardiac tissue. In consideration of a report that cardiac fibroblasts account for 20% of total mass of the myocardium [28, 29] and the considerable variation of the ratio of cell numbers of fibroblasts in heart across studies [30], we tested various ratios of MSCs (5–20%), which are used as a source of fibroblasts in CM-MSC cardiac microtissues. Therefore, a single cell suspension of CMs was mixed at a 5–20% ratio of a single cell suspension of MSCs in round bottom 96-well ultra-low attachment plates to form cardiac microtissues called spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some cis -elements in the mRNAs 3’-UTRs are also known to mediate the regulation of mRNA decay, such as PAT [29,30], ARE [31], iron-responsive element (IRE) [32], GRE [33], and MRE [34]. Many studies have demonstrated that the expression of TGFBR2 is modulated by MREs and their miRNAs in various cell types, such as miR-145 in vascular smooth muscle cells [35], miR-9-5p in hepatic stellate cells [36], miR-9 and miR-9-5p fibroblasts (HCFs) [6,37], miR-520e, miR-9-5p, and miR-135b in cancer cells [38,39,40]. Notably, miR-143 [23], miR-130a, miR-425, and miR-1306 [9] are known to target TGFBR2 in porcine GCs.…”
Section: Discussionmentioning
confidence: 99%